2018
DOI: 10.1159/000490984
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Vitamin E Protects Chickens from Newcastle Disease Virus-Mediated Exacerbation of Intestinal Oxidative Stress and Tissue Damage

Abstract: Background/Aims: Newcastle disease virus (NDV) causes a highly devastating and contagious disease in poultry, which is mainly attributed to extensive tissue damages in the digestive, respiratory and nervous systems. However, nature and dynamics of NDV-induced oxidative stresses in the intestine of chickens remain elusive. Methods: In this study, we examined the magnitude of intestinal oxidative stress and histopathological changes caused by the virulent NDV infection, and explored the protective roles of vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 51 publications
(59 reference statements)
2
26
0
Order By: Relevance
“…The ND is one of the most devastating avian diseases, infecting many different species of birds and causing high mortality and morbidity (Alexander, ; Rehman,Che et al., ). The ND is endemic in many parts of the world, including Asia, and is considered a major economic issue due to investments in vaccination and biosecurity in countries where it is theoretically controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The ND is one of the most devastating avian diseases, infecting many different species of birds and causing high mortality and morbidity (Alexander, ; Rehman,Che et al., ). The ND is endemic in many parts of the world, including Asia, and is considered a major economic issue due to investments in vaccination and biosecurity in countries where it is theoretically controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations [70][71][72] Microbial or virus challenges [73][74][75][76][77][78] Gut dis-bacteriosis [79][80][81][82][83] Pipping and hatching [5,84,85] A growing body of evidence clearly indicates that oxidative stress is involved in most of commercially relevant stresses in poultry production (for review see [1,2,15,60,86]).…”
Section: Internal Stressorsmentioning
confidence: 99%
“…Newcastle disease virus can induce oxidative stress and tissue damage in the intestine of chickens. Vitamin E supplementation alleviates this condition (Rehman et al, 2018). However, few studies have reported the relationship of DUOXs with viral infection in the intestine.…”
Section: Duox Immune Function In the Digestive Tractmentioning
confidence: 99%